Alternatif Solusi Mengatasi Problem Kepemimpinan Perempuan Di Madrasah - Muniroh, Alimul (MADINAH, 2014)
Gender issues and women's empowerment are an important issues in education, especially in the madrasa. A number of female teachers that don’t balance with women principals proved the persistence of discrimination against women in education. This article aims to identify problems experienced by women's leadership. There are three problems experienced by women in becoming the principal of the madrasah, a psychological problem, structural probblem, and socio-cultural problem. Among those three problems, socio-cultural issues are most pressing problem to be solved. With socio-cultural problem solving it can be expected to provide awareness not only for society but also for women can minimize resistance has emerged in public consciousness, and can rise fair competition in achieving a career.